Antiresonant hollow-core fiber Bragg grating design - Goel, Charu (2024)
Fiber Bragg gratings (FBGs) inscribed in hollow-core fibers hold a potential to revolutionize the field of gas photonics by enhancing the performance and versatility of hollow-core fiber-based matter cells. By effectively transforming these cells into cavities, FBGs can significantly extend the effective length of light-matter interactions. Traditional FBG inscription methods cannot be extended to hollow-core fibers, because light in the fundamental mode is predominantly confined to the hollow region where an index change cannot be induced. In this Letter, we propose a bi-thickness dual-ring hollow-core antiresonant fiber (DRHCF) design that achieves substantial overlap between the fundamental mode and cladding glass in a well-controlled manner, ensuring a strong FBG response with a minimal insertion loss. Through detailed numerical investigations, we demonstrate the feasibility of creating a high reflection FBG in the DRHCF using standard FBG inscription techniques. The proposed device is expected to have a length of <1 cm and the insertion loss of <0.3 dB, including splice loss.